2019
DOI: 10.3389/fmars.2019.00462
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Metal-Resistant Microorganisms in Deep-Sea Sediments Disturbed by Mining Activity: An Application Toward the Development of Experimental in vitro Systems

Abstract: Future mining of polymetallic nodules in the Clarion Clipperton Zone (Northeastern Pacific) is expected to affect all benthic ecosystems. The diversity, distribution, and environmental functions of microorganisms inhabiting abyssal sediments are barely understood. To understand consequences of deep-sea mining, experimental in vitro systems needs to be established to test hypotheses on the environmental impact of mining. For this, 40 bacterial strains, belonging to proteobacteria, actinobacteria and firmicutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 98 publications
1
14
0
Order By: Relevance
“…In addition, some mining proposals consider discharging a midwater sediment plume from a surface operation vessel, the plume comprising water and some sediment brought up with the nodules, nodule fines, and water used to clean the nodules aboard the vessel. Although the midwater discharge material has sometimes been referred to as tailings [3][4][5][6] , tailings are waste leftover after ore processing 7 , and to date there are no known proposals to release tailings from nodule mining operations at sea. An alternative to a midwater discharge being considered is to try and release the same material in a more localized manner close to the seabed.…”
mentioning
confidence: 99%
“…In addition, some mining proposals consider discharging a midwater sediment plume from a surface operation vessel, the plume comprising water and some sediment brought up with the nodules, nodule fines, and water used to clean the nodules aboard the vessel. Although the midwater discharge material has sometimes been referred to as tailings [3][4][5][6] , tailings are waste leftover after ore processing 7 , and to date there are no known proposals to release tailings from nodule mining operations at sea. An alternative to a midwater discharge being considered is to try and release the same material in a more localized manner close to the seabed.…”
mentioning
confidence: 99%
“…Additionally, it is difficult to give concrete recommendations for threshold values because impacts can be diverse depending on species and life stage 24 ; macro- or megafauna and adults might have a higher resistance against Cu than microbes and larvae. Especially microbial communities have gained little attention regarding ecotoxicological effects of metals in the deep-sea plains 72 , 73 despite them being an important part of the basis of the deep-sea biomass production and nutrient regeneration in polymetallic nodule fields 73 . Studies with hydrothermal vent microbes revealed that these organisms can tolerate [dCu] up to 10 µM by actively producing ligands 9 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a resistant Serratia marcescens strain, isolated from Mn mine waters in Brazil, could grow on a maximum concentration of 6 mM Mn (Barboza et al, 2017). Mn tolerance can vary widely in microorganisms, with a minimal inhibitory concentration ranging from 0.1 to 228.9 mM Mn in certain marine bacterial strains (Gillard et al, 2019). Comparisons with other strains, however, should be interpreted cautiously, since culture media composition differ among studies, and it was already observed that organic compounds in nutrient agar can chelate metals, decreasing their availability for the microorganisms tested (Polti et al, 2007;El Baz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%